Employment and unemployment in Finnish manufacturing 1985 - 95: Is technological progress the cause or the cure? - Rita Asplund; Reija Lilja (The Research Institute of the Finnish Economy (ETLA), 2000)
This paper explores employment trends and structural changes in the labour force of Finnish manufacturing over the 10-year period 1985_95 and analyses the role thereby played by technological progress. The main results may be summarised as follows. The employment- enhancing role of high-tech manufacturing industries has strengthened remarkably in Finland during the deep recession in the early 1990s. Thus, in terms of employment stability it does matter in which industry one happens to work. The structure of the labour force, on the other hand, has been re-shaped in a highly similar way irrespective of whether the industry can be classified as being high-tech or not. In other words, neither the least educated nor the oldest workers seem to have been in a more vulnerable situation in high-tech industries. The overall decline in the demand for low-skilled workers in manufacturing puts considerable pressure on re-training policies and early retirement arrangements. It is hardly realistic to assume that the jobs created in today's Finland will automatically solve the unemployment problem of the low skilled. – employment ; labour force re-structuring ; manufacturing ; technology ; unemployment – – Tässä tutkimuksessa selvitetään työvoiman rakennemuutoksia ja työllisyyskehityksen suuntaviivoja Suomen tehdasteollisuudessa vuosien 1985 ja 1995 välisellä 10 vuoden aikaperiodilla, yhdistettynä teknologisen kehityksen vaikutuksiin. Tutkimustuloksista voidaan esittää seuraava yhteenveto. Korkean teknologian toimialojen työllisyyttä kasvattava vaikutus vahvistui huomattavasti 1990-luvun alkupuoliskon laman aikana. Toimialalla on siis merkitystä työllisyystilanteen vakauden kannalta. Työvoiman rakenne on kuitenkin muuttunut samalla tavalla riippumatta toimialan teknologisesta tasosta. Toisin sanoen, iäkkäimpien ja vähiten koulutettujen työntekijöiden asema ei ole ollut sen huonompi korkean teknologian toimialoilla kuin muillakaan aloilla. Koko tehdasteollisuuden kattava heikosti koulutetun työvoiman kysynnän lasku lisää painetta järjestää toimivia uudelleenkoulutus- ja varhaiseläkejärjestelyjä. On tuskin realistista olettaa, että Suomessa nykyään syntyvät työpaikat automaattisesti ratkaisisivat heikosti koulutettujen työttömyysongelman. – työllisyys ; työvoiman rakennemuutos ; tehdasteollisuus ; teknologia ; työttömyys
Keywords: 330; Beschäftigung; Arbeitslosigkeit; Strukturwandel; Technischer Fortschritt; Finnland